Clinical Relevance of Troponin T Profile Following Cardiac Surgery - Tevaearai Stahel, Hendrik T.; Do, Peter D.; Klaus, Jeremias Bendicht; Gahl, Brigitta; Locca, Didier; Göber, Volkhard; Carrel, Thierry P. (Frontiers in Cardiovascular Medicine, 2018)
Background: Peak postoperative cardiac troponin T (cTnT) independently predicts mid- and long-term outcome of cardiac surgery patients. A few studies however reported 2 peaks of cTnT over the first 48-72 hours following myocardial reperfusion. The aim of the current study was to better understand underlying reasons of this cTnT profile and possible consequences on clinical outcome. Methods: All consecutive adult cardiac surgical procedures performed with an extra-corporeal circulation during a >6 years period were retrospectively evaluated. Patients with a myocardial infarction (MI) <8 days were excluded. cTnT profile of patients with at least one value ≥1ng/mL value were categorized according to the time occurrence of the peak value. Univariable and multivariable analysis were performed to identify factors influencing early versus late increase of cTnT values, and to verify the correlation of early versus late increase with clinical outcome. Results: Data of 5146 patients were retrieved from our prospectively managed registry. From 953 with at least one cTnT value ≥ 1ng/mL, peak occurred ≤6 hours (n=22), >6 to ≤12 hours (n=366), >12 to ≤18 hours (n=176), >18 to ≤24 hours (171), >24 hours (218). Age (OR: 1.023; CI:1.016-1.030) and isolated CABG (OR: 1.779; CI: 1.114-2.839) were independent predictors of a late increase of cTnT over a limit of 1 ng/ml (p<0.05), whereas isolated valve procedures (OR:0.685; CI: 0.471-0.998) and cross-clamp duration (OR: 0.993; CI: 0.990-0.997) independently predicted an early elevation (p<0.05). Delayed elevation over 1 ng/ml correlated with a higher rate of post-operative complications including MI (19.8% vs. 7.2%), new renal insufficiency (16.3% vs. 6.7%), MACCE (32.0% vs. 15.5%) or death (7.4% vs. 4.4%). Conclusion: Profile of cTnT elevation following cardiac surgery depends on patients’ intrinsic factors, type of surgery and duration of cross-clamp time. Delayed increase is of higher clinically relevance than prompt post-operative elevation.